PENGARUH KEBIJAKAN HUTANG, STRUKTUR KEPEMILIKAN, DAN FREE CASH FLOWTERHADAP KEBIJAKAN DIVIDEN - Andriani, Mitra Nur Fitri; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test and to analyze the influence of debt policy, ownership structure, and free cash flow to the dividend policy. The samples are manufacturing companies with a structured of institutional and managerial ownership, and to share dividend to the stakeholders which have gone public in Indonesia Stock Exchange during 2011-2014 periods. The analysis technique has been done by using multiple linear regressions analysis with the F test and multiple coefficient determinations, and the hypothesis test is done by using t test. The result of this research shows that the value of multiple coefficient determinations is 40.4% shows that simultaneously debt policy, managerial ownership, institutional ownership, and free cash flow are able to explain the variation of dividend share 40.4%. Meanwhile, the rest 59.6% is influenced by other factors outside the research. The debt policy has significant and positive influence to the dividend policy. The managerial ownership does not have any significant but positive influence to the dividend policy. The institutional ownership does not have any significant but positive influence to the dividend policy. Free cash slows do does not have any significant but positive influence to the dividend policy.Keywords:Debt Policy, Ownership Structure, Free cash flow, dividend.